(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
A field experiment was conducted In the winter season for the Rashidieh (1) site for local variety s Peas Pisum sativum L. (2021-2022) using two factors, The first factor is distances which (25,50,75), The second factor is pesticide concentrations which (750, 1,500 and 3,000 ml/ha) in addition to comparator control , Plants were randomly selected with three previous applications. the seeds of the local cultivar the data was analyzed according to the factorial experiments system using R.C.B.D significantly different treatments were distinguished with different letters .The most important results can be summarized as follow : From, the effect table of the three planting distances 25, 50 and 75 cm, it was found that there were no differences in the number of airy and thin leaves, leaves and their weight, and yield characteristics. Jungle eradication, As for the weight of the pod, seed yield and dry weight, it was found that the control treatment gave the least results, and the reason may be due to the strength of competition that occurs between the crop and its accompanying weeds in the field. control gave the highest number of broad and thin bushes and their dry weights in the three distances. As for plant height and pod length characteristic, there were no significant differences.